2015
DOI: 10.1590/0102-33062015abb0136
|View full text |Cite
|
Sign up to set email alerts
|

Environmental severity promotes phylogenetic clustering in campo rupestre vegetation

Abstract: The stress-dominance hypothesis postulates that the importance of competition in plant communities declines with increasing environmental stress while the importance of environmental filters increases. To test this hypothesis for campo rupestre vegetation, we analyzed phylogenetic diversity and community structure of angiosperm communities at two study sites within the Itacolomi State Park, Minas Gerais, Brazil. Plots representing more favorable habitats, such as those with a higher percentage of rocky outcrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 45 publications
2
15
0
Order By: Relevance
“…MNTD indicates lower phylogenetic diversity for woodlands than for shrublands, because the elevated species richness of the latter physiognomy tends to reduce MNTD values. Increasing indices of phylogenetic community structure (ses.mpd, ses.mntd, ses.pd) from grasslands to woodlands fulfill the expectations of the stress-dominance hypothesis, thus confirming the findings of similar previous studies (i.e., Gastauer & Meira-Neto 2014;Miazaki et al 2015). Positive LifeFormNRI values show that there is a tendency of related species to resemble each other more than species drawn at random from the phylogeny, indicating that close relatives share more functional traits and show higher niche overlap than expected by chance.…”
Section: Discussionsupporting
confidence: 89%
“…MNTD indicates lower phylogenetic diversity for woodlands than for shrublands, because the elevated species richness of the latter physiognomy tends to reduce MNTD values. Increasing indices of phylogenetic community structure (ses.mpd, ses.mntd, ses.pd) from grasslands to woodlands fulfill the expectations of the stress-dominance hypothesis, thus confirming the findings of similar previous studies (i.e., Gastauer & Meira-Neto 2014;Miazaki et al 2015). Positive LifeFormNRI values show that there is a tendency of related species to resemble each other more than species drawn at random from the phylogeny, indicating that close relatives share more functional traits and show higher niche overlap than expected by chance.…”
Section: Discussionsupporting
confidence: 89%
“…To date the majority of studies examining phylogenetic structure over environmental gradients in tropical plant communities have focused on climate, with only a few examining other factors such as soil fertility and even these tend to be focused on tropical trees and palms ( Lehtonen et al, 2015 ). Until recently, very few studies have focused on open vegetation formations, or on plant habits other than trees; but this is starting to change with studies on Caatinga ( Moro et al, 2015 ), campos gerais ( Moraes et al, 2016 ) and campos rupestres ( Miazaki et al, 2015 ; Pugliesi and Rapini, 2015 ). Both of the latter studies focus on campos rupestres on quartzite; and, although they differ markedly in geographic scale and taxonomic scope, they both evidence phylogenetic clustering within quartzitic campo rupestre assemblages.…”
Section: Introductionmentioning
confidence: 99%
“…Considering distribution records for a single family, the Apocynaceae, across the northern part of the Espinhaço range (widely known as the Chapada Diamantina), Pugliesi and Rapini (2015) found significant phylogenetic clustering which they attributed to niche conservatism and limited dispersal leading to in situ diversification and high density of microendemics. On a more local spatial scale, comparing the angiosperm communities on two sites within Itacolomi State Park in Minas Gerais state, Miazaki et al (2015) concluded that environmental severity reduces phylogenetic diversity and increases phylogenetic clustering in campo rupestre vegetation, as predicted by the stress dominance hypothesis ( Swenson and Enquist, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, as the more days with water excess (i.e., days with higher precipitation than evapotranspiration) cause higher sesPD and sesMPD, it is possibly because benefits the zoochory that is positively-related to mean phylogenetic distances (see zoochory discussion below). Therefore, higher precipitation promotes decreasing sesPDs and sesMPDs (i.e., phylogenetic clustering) in the TFRD similarly to effects of environmental filters found in tropical vegetation (Gastauer & Meira-Neto 2013; Miazaki et al 2015), but does not cause species richness loss. Phylogenetic effects in tropical vegetation that can be explained by plant-plant interactions, density-dependence effects (Cadotte & Tucker 2017; Carrión et al 2017; Kraft et al 2015; Meira-Neto et al 2018; Paine et al 2012), and environmental filtering that has been reported as cause of phylogenetic effects in many different groups of species, especially plants.…”
Section: Discussionmentioning
confidence: 71%